Prediction of ultimate load bearing capacity of driven piles - Wong, Charng Chen (2006)
Due to variation in soil layers, it is not easy for engineer to be assured that theoretical design of piles comply with the actual site condition. Thus, every design of piled foundations carries its own uncertainty and risk. This project evaluates the applicability of eight methods to predict the ultimate bearing capacity of spun driven friction piles. Analyses and evaluations were conducted on four piles of different sizes and lengths that failed during pile load testing. The load test interpretation methods, pile driving formulae, as well as the Meyerhof method (static analysis) were used to estimate the bearing capacities (Qp) of the investigated piles. The failure loads were the maximum measured load carrying capacities (Qm) from pile load test. The pile capacities determined using the different methods were compared with the measured pile capacities obtained from pile load tests. Three criteria were selected as basis of evaluation: the best fit line for Qp versus Qm, the arithmetic mean and standard deviation for the ratio of Qp/Qm, and the cumulative probability for Qp/Qm. Results of the analyses show that the best performing method is Butler and Hoy method (load test interpretation method). This method is ranked number one according to the mentioned criteria